Optimizing Basic Teacher Teaching Skills to Stimulate Student Learning Activities in TPA - Nina Rahayu; Safira Mayzura; Rita Sari (At-Tarbawi: Jurnal Pendidikan, Sosial dan Kebudayaan, 2023)
Teachers should be skilled in using basic teaching skills. Because these teaching skills will be able to stimulate student learning activities. However, mastering these basic teaching skills is still a common problem that is often encountered in the teaching and learning process. Departing from these problems, the purpose of this study is to reveal how teachers manage their teaching skills in the classroom and what impact they have on student learning activities at TPA Nurul A'la. The researcher used a qualitative approach. Participatory observation was used as a data collection tool. The findings in the field show that teachers have implemented the eight basic teaching skills well, and student learning activities are also very varied, the dominant activities seen are reading, listening, mental, drawing, and metric activities. So, it can be very urgent for teachers to implement these eight teaching skills in the classroom. It will have a direct effect on student learning activities. And the next influence is certainly on the learning outcomes that are increasing.